KEPRIBADIAN LOCUS OF CONTROL KARYAWAN MARKETER PADA PT. BANK PANIN DUBAI SYARIAH - Megawaty Megawaty (AkMen JURNAL ILMIAH, 2019)
The purpose of this study was to analyze the locus of control of marketing employees at PT. Bank Panin Dubai Syariah. The research is expected to be an input for companies in increasing employee work motivation seen from the personality of Locus of Control owned by marketing employees at PT. Bank Panin Dubai Syariah Makassar. The analytical tool used is interview technique which is a tool for re-checking or verification of information or information obtained previously. Interview technique used in qualitative research is in-depth interviews (in-depth interviews) is the process of obtaining information for research purposes by way of question and answer face-to-face between interviewers and informants with or without using the interview guide (guide). The results of the study indicate that the marketer funding employees at PT Bank Panin Dubai Syariah Makassar have internal locus of control personality.